Haplotype of \(TEX15\) single nucleotide variants associated with male infertility in 401 Vietnamese individuals - Nguyen, Phuong Anh; Bui, Minh Duc; Huynh, Thi Thu Hue; Nguyen, Thuy Duong (Academia Journal of Biology, 2024)
Spermatogenesis is a process of cell differentiation to produce fertilized sperm. Testis-expressed 15 (TEX15), an important gene in spermatogenesis, has been reported to be linked with male infertility in various populations. This study aimed to assess the association of single nucleotide polymorphism (SNP) TEX15 rs323347 with male infertile individuals in a Vietnamese cohort and further analyze the haplotypes of TEX15 rs323346 and TEX15 rs323347. A total of 401 unrelated males, including 202 male infertility patients and 199 healthy controls were genotyped for TEX15 rs323347 using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Using statistical methods, the results showed that the allele frequencies of TEX15 rs323347 were in agreement with Hardy-Weinberg equilibrium (HWE) (p-value > 0.05), but its genotype frequencies were not significantly different between male infertility patient and control groups (p-values > 0.05). However, the CA haplotype of the two variants (rs323346 and rs323347) increased the risk of male infertility (p = 0.046, OR = 2.547, 95% CI = 0.982–6.602). Thus, this study would enrich the knowledge of the impact of genetic factors on male infertility in the Vietnamese population.